THE REPRESENTATION OF GARUDA CHARACTER IN A COMIC ENTITLED GARUDAYANA SAGA BY IS YUNIARTO - Bestania, Dhityana Ayu; Yuwono, Prapto (International Review of Humanities Studies, 2023)
Garudayana Saga is a comic that tells the story of Garuda. Garudayana Saga has the concept of Garuda, which is also found in Adiparwa. Adiparwa is the first book of the Mahabharata story. The Garuda character in the Adiparwa narrative is illustrated with manga-style drawings in Garudayana Saga. This research aims to explain the representation of the Garuda character seen in the Garuda character image in the Garudayana Saga, based on a quote that contains the character of Garuda in Adiparwa. The research is conducted using Creswell's qualitative method (2014), combined with Damono's transmedia theory (2018) and Peirce's semiotic theory (1998). Overall, the character of Garuda in Garudayana Saga is maintained based on Garuda in Adiparwa, which can be seen in physical characteristics, the title of king, supernatural powers, nature, and appetite, with the addition of accessories worn by the Garuda character in the comic. Then, found a sign in the form of 3 icons, 1 index, and 3 symbols. The results of this study reveal that the representation of the Garuda character in Garudayana Saga, which is in the form of a manga-style drawing, is compatible with the Garuda character in Adiparwa's narrative. We can conclude that the Garuda character in Garudayana Saga is correctly represented with a manga-style drawing based on the Garuda character in Adiparwa.